Measurements of long-term strength changes due to cyclic loading in Gulf of Mexico clay - Fauzan, Sahdi; Joe G., Tom; Noor, Laham; Phil, Watson; Fraser, Bransby; Christophe, Gaudin (2020)
Many types of deep-water offshore infrastructure are subject to cyclic movements during their design life. It is acknowledged that cyclic movement in normally consolidated clay causes the undrained strength to decrease through remoulding; but the strength can also recover (through reconsolidation) if dissipation of excess pore pressure is allowed to occur. In many offshore environments however, the soil profile is overconsolidated, especially near the mudline – and it is less clear how stress history affects remoulding and reconsolidation behaviour. Furthermore, previous testing to investigate this effect has mostly been conducted in ‘laboratory’ kaolin clay, and whether these results reflect the behaviour of natural clays is less known. To address these uncertainties, a series of long-term cyclic T-bar tests were performed in samples of reconstituted Gulf of Mexico (GoM) clay prepared at overconsolidation ratios (OCR) of 1 and 10. Episodic cyclic penetrometer tests were performed at peak-to-peak displacement amplitudes of four penetrometer diameters, followed by wait periods of 10 hours in between each episode. This paper confirms that soil strength can increase in normally consolidated natural clay (although the increases are smaller than those seen in kaolin), while also highlighting how the OCR affects the strength changes after reconsolidation is allowed to occur.